Evaluation of Residential Carbon Neutrality Through Carbon Emissions, Vegetation Carbon Sequestration, and Occupant Energy Behavior - Abellani Yulitasari; Popi Puspitasari (Green Publisher Indonesia, 2026)
This study evaluates residential carbon neutrality by examining carbon emissions, vegetation carbon sequestration, and occupant energy behavior within urban housing. Global warming, driven by carbon dioxide emissions, underscores the need for integrated solutions addressing household carbon footprints. The objective of this research is to develop a comprehensive model that incorporates building carbon emissions, vegetation carbon sequestration, and occupant behavior to assess residential carbon neutrality. This study focuses on 49 households in Vila Dago Housing, Pamulang, South Tangerang, utilizing surveys and field data to estimate energy consumption, carbon emissions, and vegetation absorption. The findings reveal that operational carbon emissions are primarily driven by electricity usage, with average emissions ranging from 10,000 to 27,000 kg CO₂e annually per household. Embodied carbon emissions from construction materials also contribute significantly, with variations depending on house type. Vegetation in the study area provides limited carbon sequestration, unable to offset the carbon emissions generated by household activities. Additionally, occupant behavior, including lighting, air conditioning, LPG use, and waste management, directly influences overall emissions. In conclusion, achieving carbon-neutral housing requires improved energy behavior and enhanced green spaces, with an integrated approach to passive building design and carbon sequestration strategies being essential for mitigation efforts.